Enhanced Surface Interactions Enable Fast Li+ Conduction in Oxide/Polymer Composite Electrolyte. (23rd January 2020) - Wu, Nan; Chien, Po‐Hsiu; Qian, Yumin; Li, Yutao; Xu, Henghui; Grundish, Nicholas S.; Xu, Biyi; Jin, Haibo; Hu, Yan‐Yan; Yu, Guihua; Goodenough, John B.
Abstract: Li + ‐conducting oxides are considered better ceramic fillers than Li + ‐insulating oxides for improving Li + conductivity in composite polymer electrolytes owing to their ability to conduct Li + through the ceramic oxide as well as across the oxide/polymer interface. Here we use two Li + ‐insulating oxides (fluorite Gd0.1 Ce0.9 O1.95 and perovskite La0.8 Sr0.2 Ga0.8 Mg0.2 O2.55 ) with a high concentration of oxygen vacancies to demonstrate two oxide/poly(ethylene oxide) (PEO)‐based polymer composite electrolytes, each with a Li + conductivity above 10 −4  S cm −1 at 30 °C. Li solid‐state NMR results show an increase in Li + ions (>10 %) occupying the more mobile A2 environment in the composite electrolytes. This increase in A2‐site occupancy originates from the strong interaction between the O 2− of Li‐salt anion and the surface oxygen vacancies of each oxide and contributes to the more facile Li + transport. All‐solid‐state Li‐metal cells with these composite electrolytes demonstrate a small interfacial resistance with good cycling performance at 35 °C. Abstract : Die starke Wechselwirkung zwischen den Oberflächen‐Sauerstoffvakanzen von GDC/LSGM und den TFSI − ‐Anionen im Komposit‐Polymerelektrolyten verändert die Li + ‐Verteilung in zwei lokalen Umgebungen. Die gestiegene Population mobiler Li + ‐Ionen in A2 erhöht deutlich die Li + ‐Leitfähigkeit des Komposit‐Elektrolyten.